Understanding mycobacterial genome diversity using a cultureomics approach - Seemi, Palesa (My University, 2022)
Tuberculosis (TB), caused by the pathogen Mycobacterium tuberculosis (M. tb), claims millions of lives each year and is one of the leading causes of death worldwide. One of the many challenges to the eradication of this disease is the presence of heterogeneous bacterial populations within the host or infection with different strain types, especially if the metabolically quiescent population harbours drug resistance. The different growth requirements for bacteria complicate the detection of such infections in sputum because the type of growth media used selects for the fitter strain/genotype in culture, resulting in the overrepresentation of actively dividing populations compared to the minority metabolically quiescent, non-replicating populations in sputum. The purpose of this study was to determine whether culturing sputum in axenic media (with and without growth factor supplementation) which promote the enumeration of minority bacterial populations in sputum, revealed genetically distinct genotypes in sputum. This was achieved by comparing the genomic sequence obtained from uncultured sputum to the genomic sequences obtained from the same sputum sample that has been cultured under different growth conditions. This study also aimed to investigate within-host strain dynamics in mixed strain M. tb infections using an artificial mixed strain infection model. Results revealed that sputum culture under various growth conditions resulted in an increase in the observed genetic diversity in sputum due to the emergence of different strain types and heterogeneous bacterial populations from the same infecting strain. Furthermore, culturing was shown to be selective of a specific genotype in sputum. The mixed strain infection model required additional time for optimization. Conclusively, this study showed that whole genome sequencing is a useful tool for detecting additional strain types in sputum and that minority populations present in sputum are genetically heterogeneous and require different types of growth media to emerge in sputum.
A dissertation submitted in fulfilment for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg,2022.